The Making of Singapore As an Asian Regional Corridor : Historicity, Trade, and Diaspora - Hong Liu; Cheun Hoe Yow; Huimei Zhang (Routledge, 2026)
Liu, Yow, Zhang and the contributors examine Singapore's significance as an Asian Regional Corridor and provide a new perspective on interpreting Singapore's important position in the Asian region and its role as a bridge connecting Asia to the world and within the Asian region.The book unfolds from three interconnected perspectives: historicity, trade, and diaspora, examining Singapore as an Asian regional corridor and its pivotal role in global political, economic, and social developments. It also delves into current mobility trends and future challenges, contributing to a nuanced understanding of Singapore's and Southeast Asia's uncertain trajectory and offers a unique perspective that collectively illuminates the diverse dimensions of Singapore's influence and engagement in the global stage.This book is a valuable resource for scholars and students of Southeast Asian studies including political, economic, and cultural studies and those interested in Singapore's development and its regional role in Asia. It would also be of interest to those conducting comparative research on Global Asia and its interactions with the world.